1996
DOI: 10.1523/jneurosci.16-11-03620.1996
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Potentiates Kainate-Induced Currents via Activation of the cAMP Cascade

Abstract: Evidence for nongenomic actions of steroids is now coming from a variety of fields of steroid research. Mechanisms of steroid action are being studied with regard to the membrane receptors and the activation of second messengers. The present study investigated the mechanism for the rapid effect of estrogen on acutely dissociated hippocampal CA1 neurons by using the whole-cell, voltage-clamp recording. Under the perforated patch configuration, 17P-estradiol potentiated kainateinduced currents in 38% of tested n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
195
3
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(216 citation statements)
references
References 58 publications
16
195
3
2
Order By: Relevance
“…Hence, effects of steroids with a latency of 10 minutes or less are often attributed to non-classical actions. For example, in dissociated hippocampal cells, E 2 increases kainate-induced currents in 3 minutes [23]. We have demonstrated that administration of E 2 improves affective processes within 10 minutes of administration when administered directly to the hippocampus [24], which supports the idea that some of E 2 's effects in the hippocampus for these processes are rapid.…”
Section: Rapid And/or Membrane Actions In the Hippocampus For E 2 'S supporting
confidence: 71%
“…Hence, effects of steroids with a latency of 10 minutes or less are often attributed to non-classical actions. For example, in dissociated hippocampal cells, E 2 increases kainate-induced currents in 3 minutes [23]. We have demonstrated that administration of E 2 improves affective processes within 10 minutes of administration when administered directly to the hippocampus [24], which supports the idea that some of E 2 's effects in the hippocampus for these processes are rapid.…”
Section: Rapid And/or Membrane Actions In the Hippocampus For E 2 'S supporting
confidence: 71%
“…However, we did not see any effects of 17α-estradiol on the GABA B response [17] or the μ-opioid response [21]. Similarly, Gu and Moss found that 17α-estradiol did not mimic the actions of E 2 in the hippocampus to potentiate the glutamate (kainate)-mediated currents in CA1 pyramidal neurons [35]. Likewise, Mermelstein et al found that 17α-estradiol was much less efficacious than E 2 in reducing L-type calcium currents in neostriatal neurons [36].…”
Section: Mer Is a Gpcr In Hypothalamic Pomc Neuronscontrasting
confidence: 46%
“…It was known previously that E 2 could rapidly modulate synaptic efficacy via activation of PKA [21,35,69,70]. Recently, we have delineated the upstream components of this signaling pathway that includes Gαq, phospholipase C, and PKCδ activation.…”
Section: Significancementioning
confidence: 99%
“…Also, E2 potentiates non-NMDA (kainate)-mediated excitation of hippocampal CA1 pyramidal neurons via activation of a cAMP/PKA pathway Moss, 1996, Gu andMoss, 1998). Based on the findings from the hippocampal slice, it was hypothesized that E2 activates a Gs-coupled receptor on the extracellular surface of hippocampal neurons, which operates in concert with an internal action of E2 on cAMP-dependent phosphorylation (Gu and Moss, 1998).…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 99%